Aplikasi TOEFL Institusional Berbasis Web (Studi Kasus: UPT Pusat Bahasa Universitas Teknologi Sumbawa) - Rizka Irjiba; Shinta Esabella; Yana Karisma (Bulletin of Information Technology (BIT), 2023)
This study aims to design and build an Institutional TOEFL Application to make it easier for UPT Language Center UTS to correct test takers' answers. The Institutional TOEFL implementation method that is still running at the UPT UTS Language Center is still carried out non-digitally using a paper test. The participants answer the questions, and then the UPT Language Center UTS corrects the answers, then counts the number of correct questions, and calculates the total score the test takers get. With the Institutional TOEFL Application, it is hoped that it will be able to improve the quality of performance and provide convenience for UPT Language Center UTS in processing test participant data to be more effective and efficient. The web-based application is built using the help of the PHP programming language and MySQL database using the waterfall method framework. System planning uses a structured method by defining context diagrams, DFD and ERD, and is tested using the beta testing method. Based on the test results, out of 8 questions with 20 respondents where the answer "Yes" was 87.5% and the answer "Enough" was 12.5%, the Institutional TOEFL Application is in accordance with user needs, and is suitable for use at UPT Language Center UTS. The results of this study are the web-based UPT Institutional TOEFL Application UTS Language Center which can be accessed by the public so that it can contribute to the convenience of test takers in carrying out the Institutional TOEFL